Multifactorial intervention for diabetes control among older users of insulin - Machry, Rafael Vaz; Pedroso, Henrique Umpierre; Vasconcellos, Luthiele Silva; Nunes, Rafaela Ramos; Evaldt, Cibelle de Abreu; Yunes Filho, Eduardo Bardou; Rodrigues, Ticiana da Costa (Revista de Saúde Pública, 2018)
OBJECTIVE: To evaluate if the closer follow-up with the supply of insulin pens and the measurement of capillary blood glucose improve the management of older patients with type 2 diabetes without adequate glycemic control despite extensive therapy. METHODS: This is a prospective, non-randomized, quasi-experimental study. We have included 45 patients over 60 years old, from both sexes, with glycated hemoglobin (HbA1c) > 8.5% using oral hypoglycemic agents and insulin. The intervention consisted of monthly medical visits, with the provision of insulin pens and strips for blood glucose measurement. All patients received insulin pen, refills of Neutral Protamine Hagedorn and regular insulin, needles for the pen, blood glucose meter, and capillary blood glucose tests (three tests/day). Treatment was adjusted with the same endocrinologist monthly for six months. Glycated hemoglobin was measured at baseline and 12 and 24 weeks after intervention. RESULTS: Glycated hemoglobin at baseline was 10.34% (SE = 0.22%) and 8.54% (SE = 0.24%, p < 0.001) and 8.09% (SE = 0.21%, p < 0.001) at 12 and 24 weeks after intervention, respectively, with a significant reduction from baseline. CONCLUSIONS: More frequent medical visits, with treatment inputs including the use of insulin pens and self-monitoring, have improved glycemic control (reduction of 2.25% in HbA1C, on average, at 24 weeks of follow-up). Our data support a change in the management and medical behavior of older patients with chronically decompensated diabetes.